Investigation into the impact of embedded generators on distribution system performance using theorem of superposition - Ciric, Rade M.; Nouri, Hassan; Feltrin, Antonio Padilha [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2005)
Since the 1980s, huge efforts have been made to utilise renewable energy sources to generate electric power. One of the interesting issues about embedded generators is the question of optimal placement and sizing of the embedded generators. This paper reports an investigation of impact of the integration of embedded generators on the overall performances of the distribution networks in the steady state, using theorem of superposition. Set of distribution system indices is proposed to observe performances of the distribution networks with embedded generators. Results obtained from the case study using IEEE test network are presented and discussed.
Keywords: Distribution networks; Embedded generators; Power systems modelling; Theorem of superposition; Computer networks; Distributed parameter networks; Energy conservation; Renewable energy resources; Water distribution systems; Electric power distribution